Macroscopic and Histopathologic Findings From a Mass Stranding of Rough-Toothed Dolphins (Steno bredanensis) in 2005 on Marathon Key, Florida, USA - Ewing, Ruth Y.; Rotstein, David S.; McLellan, William A.; Costidis, Alexander M.; Lovewell, Gretchen; Schaefer, Adam M.; Romero, Carlos H.; Bossart, Gregory D. (Frontiers in Veterinary Science, 2020)
On March 2, 2005 approximately 70 rough-toothed dolphins (Steno bredanensis) mass stranded along mud flats and associated canals on the Atlantic Ocean side of Marathon Key, Florida. Forty-six were necropsied and placed into two groups for analysis: Group-1 animals (N = 34; 65%)) that died prior to medical intervention and rehabilitative efforts and Group-2 animals (N =12; 35%) that died in rehabilitation. Thirty-four animals were females (18 adults, 5 juvenile/subadult, 7 calves, and 4 of undetermined age) and 12 were males (6 adults, 4 juvenile/subadults, 1 calf, and 1 of undermined age). Body condition overall was fair to good in Group-1 and fair to poor in Group-2. Lesions were observed in multiple body systems Greater than 90% of animals in both groups had respiratory lesions. Verminous sinusitis and bronchopneumonia were 2-3 times more prevalent in Group-2. Capture/exertional rhabdomyolysis was observed in Group-2 (42%) Vacuolar hepatopathies were observed in both groups including hepatic lipidosis (Group-1) and mixed etiologies (Group-2). Pancreatic and gastrointestinal tract pathologies were prevalent in Group-2 animals 56% and 75%, respectively and included gastritis, gastric ulceration, enterocolitis, pancreatic atrophy, and pancreatitis related to physiologic stress. Group-2 more frequently had evidence of hemorrhagic diathesis present which included increased extramedullary hematopoiesis in various organs, increased hemosiderosis, and hemorrhage and hemorrhagic drainage in various organs. Central nervous system disease, primarily edema and mild inflammation were equally prevalent. Renal proteinuria, tubular necrosis and pigmentary deposition were observed in Group-2. Dental attrition was observed in approximately 40% of the groups. Gammaherpesviral-associated pharyngeal plaques were observed in 46 and 54% of Group-1 and 2 animals, respectively. Other lesions observed were mild and incidental with a frequency rate less than 20%. The findings from this Steno stranding provide a unique window into baseline individual and population clinical conditions and additional perspective into potential clinical sequelae of rehabilitation efforts.